(+)- and (−)-trichodermatrione A: a pair of enantiomers with a cyclobutane-containing skeleton from the endophytic fungus Trichoderma sp. EFT2. (April 2022) - Yan, Wei; Ji, Wenxia; Ping, Chuan; Zhang, Tianyi; Li, Yu; Wang, Biao; Chen, Tianyu; He, Bo; Ye, Yonghao
Abstract: (±)-trichodermatrione A, a pair of cyclobutane-containing enantiomers with an undescribed tricyclic 6/4/6 skeleton, was isolated from Trichoderma sp. EFT2, an endophytic fungus from Euonymus fortunei (Turcz.) Hand.-Mazz (Celastraceae). The racemates were separated by chiral HPLC with the structures elucidated by a combination of MS, NMR, ECD calculation and X-ray crystallography analyses. (±)- trichodermatrione A and enantiomers were found to be antibacterial against phytopathogenic bacteria Xanthomonas oryzae pv. oryzae ( Xoo ) and X. oryzae pv. oryzicola ( Xoc ). Graphical abstract: (±)-trichodermatrione A, a pair of cyclobutane-containing enantiomers with an undescribed skeleton, was isolated from the plant endophytic fungus Trichoderma sp. EFT2. Image 1 Highlights: (±)-trichodermatrione A represents an undescribed tricyclic 6/4/6 skeleton. Racemates were separated by chiral HPLC. Structures were elucidated by 2D NMR, ECD and X-ray analysis. Isolated compounds showed moderate antibacterial activity.